Genome-Wide Identification and Analysis of the Ascorbate Peroxidase (APX) Gene Family of Winter Rapeseed (Brassica rapa L.) Under Abiotic Stress - Ma, Li; Qi, Weiliang; Bai, Jing; Li, Haiyun; Fang, Yan; Xu, Jia; Xu, Yaozhao; Zeng, Xiucun; Pu, Yuanyuan; Wang, Wangtian; Liu, Lijun; Li, Xuecai; et al. (Frontiers in Genetics, 2022)
Winter Brassica rapa (B. rapa) is an important oilseed crop in northern China, but the mechanism of its cold resistance remains unclear. Ascorbate peroxidase (APX) plays important roles in the response of this plant to abiotic stress and in scavenging free radicals. In this study, the roles of APX proteins in the cold response and superoxide metabolism pathways in both rapeseed species were investigated, and a comprehensive analysis of phylogeny, chromosome distribution, motif identification, sequence structure, gene duplication, and RNA-seq expression profiles in the APX gene family was conducted. Most BrAPX genes were specifically expressed under cold stress and behaved significantly differently in cold-tolerant and cold-sensitive varieties. Quantitative real-time-PCR (qRT-PCR) was also used to verify the differences in expression between these two varieties under cold, freezing, drought and heat stress. The expression of five BrAPX genes was significantly upregulated in growth cones at 3 h of cold stress, while their expression was significantly lower at 24 h than at 3 h. The expression of Bra015403 and Bra003918 was significantly higher in ‘Longyou-7’ growth cones than in other treatments. Five BrAPXs (Bra035235, Bra003918, Bra033040, Bra017120, and Bra031934) were closely associated with abiotic stress responses in B. rapa. These candidate genes may play important roles in the response of B. rapa to low temperature stress and provide new information for the elucidation of the cold resistance mechanism in B. rapa.